Legitimacy of Police Assistance Requests in Pursuit Without Police Report: A Review of the Case of Shooting a Car Rental Boss by TNI AL Personnel - Malik, Muhamad Rizki (International Journal of Business, Law, and Education, 2025)
Law enforcement in Indonesia often experiences significant difficulties, especially regarding state apparatus. This study investigates the case of the shooting of a car rental entrepreneur by members of the Indonesian Navy. It assesses the legitimacy of police actions that rejected the request of the victim's family in an emergency without an official report. The goal is to determine the legitimacy of police actions that reject the request of the victim's family in an emergency. The normative juridical method used is a case study. This method analyzes the literature, regulations, expert opinions, legal documents, and legal legitimacy theory of Soerjono Soekanto. The results show that although police reports are administratively necessary, procedures must be flexible in emergencies to guarantee legal protection. An over-reliance on formal processes can hinder access to substantive justice. To maintain public legitimacy and trust in policing, this study emphasizes the importance of policy reform to balance legal compliance and operational responsiveness.